PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN DAN LOYALITAS PASIEN RAWAT JALAN - Putri Giovaningrum; Andra Fristasya (Journal of Hospital Administration and Management, 2020)
Service quality provides an impetus to service users to establish ties with service providers. In the long term, such a bond allows service providers to understand customer expectations. According to data from the Director General of Health Efforts at the Ministry of Health, the number of hospitals in Indonesia as of May 2012 has reached 1,959 units. 785 government hospitals or more than 50% are private hospitals. The trend of increasing the number of hospitals which is increasing year by year indicates that hospitals must be able to compete. Therefore, hospitals that have been established and operating at this time must be able to create and maintain quality hospital health services for their customers so that they do not move to other hospitals. Method : Literature Review is conducted based on the issue, methodology. Of the 2 studies used, 1 of them used an analytical method with a cross sectional approach. Results: Based on the results of the study, it was found that service quality had an effect on patient satisfaction and loyalty in the hospital